1978
DOI: 10.1073/pnas.75.7.3464
|View full text |Cite
|
Sign up to set email alerts
|

Failure of autologous mixed lymphocyte reactions between T and non-T cells in patients with systemic lupus erythematosus.

Abstract: Normal human T cells proliferate vigorously when stimulated with autologous non-T cells. This autologous mixed lymphocyte reaction (MLR) between T and non-T cells was defective in patients with active systemic lupus erythematosus (SLE) In contrast, T cells and non-T cells from active SLE patients behaved normally as responding and stimulating cells, respectively, in the allogeneic MLR. Systemic lupus erythematosus (SLE) is a complex multisystem autoimmune disease. One of its most prominent features is the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
102
1
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(113 citation statements)
references
References 15 publications
9
102
1
1
Order By: Relevance
“…Thus, the decreased Con A-induced suppressor activity in patients with PBC may represent a close relation to the reduction of AMLR. The same defect of both Con A-induced suppressor activity and AMLR has been reported in patients with systemic lupus erythematosus (Sakane and Steinberg 1978) and with chronic active hepatitis (Nonomura et al 1982). Our present data suggest that serum factor(s) inhibitory to lymphocyte transformation responses by Con A and PHA are present in a majority of patients with PBC.…”
Section: Ailrsupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, the decreased Con A-induced suppressor activity in patients with PBC may represent a close relation to the reduction of AMLR. The same defect of both Con A-induced suppressor activity and AMLR has been reported in patients with systemic lupus erythematosus (Sakane and Steinberg 1978) and with chronic active hepatitis (Nonomura et al 1982). Our present data suggest that serum factor(s) inhibitory to lymphocyte transformation responses by Con A and PHA are present in a majority of patients with PBC.…”
Section: Ailrsupporting
confidence: 66%
“…Derangement of suppressor T cell function has been reported in various human diseases such as hypogammaglobulinemia (Siegal et al 1976), Hodgkin's disease (Twomey et al 1975), systemic lupus erythematosus (Sagawa and Abdou 1979), ulcerative colitis and Crohn's disease (Hodgson et al 1978a), juvenile rheumatoid arthritis (Strelkauskas et al 1978), chronic active hepatitis (Hodgson et al 1978b; Nonomura et al 1982) and insulin-dependent diabetes mellitus (Buschard et al 1980). Recently, autologous mixed lymphocyte reaction (AMLR), in which human T cells respond to mitomycin-C treated or X-irradiated autologous non-T cells, is employed to investigate immunoregulatory functoins (Sakane and Steinberg 1978). AMLR was found to be decreased in patients with systemic lupus erythematosus (Sakane and Steinberg 1978), Sjogren's syndrome (Miyasaka et al 1980) and chronic activie hepatitis (Nonomura et al 1982 …”
mentioning
confidence: 99%
“…Recently, we have found that the autologous mixed lymphocyte reaction is markedly diminished in patients with active SLE and decreased in some patients with inactive SLE (4 …”
Section: In Normal Individuals T Cells Are Stimulated To Proliferate mentioning
confidence: 99%
“…1977;Engleman et al, 1982). Early investigations demonstrated abnormal AMLR in patients with lymphoproliferative and autoimmune diseases (Sakane, Steinberg & Green, 1978;Miyasaka et al, 1980;Engleman et al, 1980), and consequently this assay has gained increasing use in the clinical assessment of immunity. Also, because both effector (cytotoxicity and antibody production) and regulatory (help and suppression) functions are generated during in vitro culture, the AMLR has been used to study interactions between mononuelear eell subsets (Tomanari, 1980;Gatenby, Kotzin & Engleman, 1981;Kotani et al, 1984).…”
Section: Introductionmentioning
confidence: 99%